Costa Rica as a Destination for Migrants in Need of International Protection: IMR Country Report - Weitzman, Abigail (2022)
In this IMR Country Report, we draw attention to Costa Rica as a strategic location for expanding research and theory on migrants in need of protection (MNP), who have migrated abroad primarily to evade an imminent threat to their survival. MNP constitute an increasing share of all international migrants in Costa Rica and worldwide, yet research on these migrants and their migration dynamics remains comparatively underdeveloped relative to research on migrants who relocate abroad primarily in pursuit of material gains, social status, or family reunification. As we highlight, Costa Rica is an instrumental site to deepen understandings of MNP populations and migration dynamics because its large and rapidly growing MNP population is incredibly diverse with respect to national origins, demographic characteristics, and underlying motivations for migration. This diversity presents ample opportunities to better understand heterogeneity in the different types of threats MNP seek to evade; how and why MNP incorporation is shaped by individuals’ demographic attributes and pre-migration threats; and how the social networks of various MNP subpopulations develop and overlap with time. Moreover, the geographic concentration of MNP in two regions in Costa Rica lends itself to primary data collection among this population and generates opportunities for estimating local MNPs’ demographic characterization, even in the absence of a reliable sampling frame.